PERANAN KOPERASI SIMPAN PINJAM DHANA ARTHA DALAM MEMBANGUN PEREKONOMIAN DAN MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA BUALU - Maria Rita; I Made Sujana; Dessy Widyanasari; Putu Ratna Windusara Putri; Ni Kadek Noviyanti (Nusantara Hasana Berdikari, 2022)
In economic activities,cooperatives play a role in helping the economic development of the community by empowering.Where empowerment is an effort to meet the needs desired by individuals, groups and the Bualu village community so that they have the ability to make choices and control their environment in order to fulfii their desires, including their accessibility to resources releted to their work, social activites and other,etc. The purpose of this study was to determine the role of the savings and loan coorperative Dhana Artha in improving the econommy of the community in Bualu village, to the determine the efforts of the Dhana Artha savings and loan cooperative in improving the econommunity of the community in Bualu vilalge, and to determine the level of welfare of the community in Bualu village who are members of the savings cooprative borrow Dhana Artha.This type of research is filed research with ten respondents.the type of data is qualitative data.the data sources are primary data and secondary data.methods of data collection using observation,interview,and documentation.the data analysis technique used was the Miles and Hubermand model. The results of this study indicate that the Dhana Artha savings and loars cooperative has an effort to empower the community in improving the welfare indicotors have been fulfilled.The steps used in community economic empowerment are (enabling)creating an atmosphere or climed that allows potential community develops(empower)strengthens the potential and power of the community.With the existence of the Dhana Artha savings and loan cooperative in Bualu village,it plays an active role in improving the quality of human life for the community and increasing the income of the community,the Dhana Artha savings and loan cooperative provides capital loan products ained at helping people who need funs. Suggestions to always remind people of better service to the commuity,especially those who are members of the Dhana Artha savings and loar cooperative so that they can improme the welfare of the community.